Antioxidant Activity of Banana Kepok Kuning (Musa paradisiaca L.) and Cavendish (Musa acuminata Colla, AAA) Peel Extracts and the Potential as Chicken Meat Preservative - Afifah Afifah; Taufik Adhi Prasetya Wardana; Tri Rini Nuringtyas (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
Bananas are a type of fruit that is consumed, with the peel being discarded as waste. However, the peel contains phytochemical compounds, including phenolic and flavonoids, which act as natural antioxidants. Therefore, this study aimed to determine the antioxidant activity of banana peel of Kepok Kuning (KCE) (Musa paradisiaca L.) and Cavendish (CCE) (Musa acuminata Colla, AAA) extracts, as well as eluviate their preservative potency. The sample was extracted using 80% methanol, and the antioxidant activities of KCE and CCE were evaluated using DPPH and FRAP. The extracts and the control antioxidant butylated hydroxyl toluene (BHT) were tested for their preservatives potency on chicken meat at concentrations of 5%, 10%, and 15%, respectively. After 8 days of incubation in the refrigerator, the color change was recorded and analyzed using ImageJ, while free fatty acid contents were determined by titration. The results showed that 15% KCE and 15% CCE exhibited higher antioxidant activities than 0.1% BHT. There was no significant difference in the L (lightness) and b (yellowness) values between the treatments, but variations were evident in the a (redness) values. FFA values were significantly different between treatments, with untreated control registering the highest value at 0.41%, and the KCE 15% and CCE 15% concentrations showing the lowest values at 0.12%. Considering these results, both extracts could be developed as preservatives for chicken meat.